2020
DOI: 10.1093/braincomms/fcaa191
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic modelling and therapeutic monitoring of immune-mediated necrotizing myopathy: role of electrical myotonia

Abstract: Delayed diagnosis of immune mediated necrotizing myopathy (IMNM) leads to increased morbidity. Patients with chronic course without HMGCR-IgG (3-hydroxy-3-methylglutaryl-coenzyme-A reductase) or SRP54-IgGs (signal recognition particle) are often challenging to diagnose. Immunotherapy response can also be difficult to assess. We created a statistical model to assist IMNM diagnosis. Electrical myotonia vs fibrillations were reviewed as biomarkers for immunotherapy treatment response. Identified were 119 IMNM cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…7 This AI-ECG algorithm may provide a potential new tool to assist monitoring beyond CK values, direct manual strength, and electromyographic testing. 8 Specifically, we note a significant improvement of AI-ECG-predicted LVD probability scores in patients while on immunotherapy. However, our study has limitations to address this point given the lack of uniform follow-up with echocardiograms in all patients.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…7 This AI-ECG algorithm may provide a potential new tool to assist monitoring beyond CK values, direct manual strength, and electromyographic testing. 8 Specifically, we note a significant improvement of AI-ECG-predicted LVD probability scores in patients while on immunotherapy. However, our study has limitations to address this point given the lack of uniform follow-up with echocardiograms in all patients.…”
Section: Discussionmentioning
confidence: 66%
“…7 The decision to escalate immunotherapy is complex but can be guided by the level of muscle breakdown creatine kinase (CK) enzyme, electromyographic findings (fibrillations and myotonia) and direct manual muscle testing. 8 Patients with cardiorespiratory involvement are likely to benefit from early and more aggressive immunotherapy given the risk of development of cardiac fibrosis, which is irreversible. 9,10 International guidelines have now recommended that all patients with IIM undergo electrocardiogram (ECG), with echocardiograms reserved for those with orthopnea, chest pain, or syncope.…”
mentioning
confidence: 99%
“…The 27 studies included in the review consisted of seventeen non-comparative studies (nine descriptive cross-sectional studies [ 9 , 14 , 16 , 17 , 22 , 23 , 29 , 36 , 38 ], seven case reports [ 27 , 28 , 31 35 ] and one case series [ 30 ]), six analytical cross-sectional studies [ 15 , 18 – 20 , 24 , 37 ], one time series with comparison group [ 21 ] and three retrospective cohort studies [ 25 , 26 , 41 ]. Studies were from multiple countries, including nine from Europe [ 9 , 15 , 16 , 25 , 27 , 31 , 35 , 37 , 38 ], eight from the United States [ 20 , 21 , 24 , 29 , 30 , 33 , 34 , 41 ], three from Australia [ 19 , 22 , 23 ], one from New Zealand [ 14 ], two from Asia [ 28 , 32 ], and one from South America [ 26 ]. Two studies were multi-national [ 18 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were multi-national [ 18 , 36 ]. Studies reported diagnostic delay in all IIM subtypes; DM [ 28 , 29 , 33 ] (n = 3 studies), IBM [ 9 , 14 , 16 , 17 , 21 – 24 , 27 , 30 , 34 36 ] (n = 13 studies), ASS [ 18 , 26 , 31 , 32 ] (n = 4 studies), JDM [ 15 , 20 ] (n = 2 studies), NM [ 41 ] (n = 1 study) and mixed or all types of IIM [ 19 , 21 , 25 , 38 ] (n = 4 studies). In total, based on the IIM subtypes, the systematic review included a sample size of 1827 with the highest sample size for IBM (n = 1262 people) [ 9 , 14 , 16 , 21 – 24 , 27 , 30 , 34 36 ] and the lowest for NM [ 41 ] (n = 67 people).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation